MOTIF TEKSTIL SEBAGAI VALUE PROPOSITION KOLEKSI BRAND FESYEN YANG MARKETABLE - PAULINA TJANDRAWIBAWA (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2018)
Fashion industry in Indonesia is increasing from year to year and so does the competition between fashion brands. The Indonesian Creative industry players by 2020 to grow by 8.4 million and dominated by young adults. With the many fashion brands that emerge, a brand needs more value propositions to make their product stand out and marketable. This journal will present how graphic motif on textile can be used by fashion brands as their product’s value proposition and convert it into marketable products. Research method will be presents through qualitative method in the form of direct interview with fashion brand owner and supported by literature study and observation. This writing aims to help fashion business owners to comprehend the design concept as value position for their collection. Keywords: fashion, motif; pattern; textile; value proposition